Relationship between Anxiety and Breast Milk Expulsion in Lactating Mothers - Rohma, Annisa Nur; Utomo, Martono Tri; Etika, Risa; Ningtyas, Woro Setia (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Breastfeeding is the process of giving mother's milk to babies from birth to two years. Exclusive breastfeeding can protect babies and children against dangerous diseases and strengthens the affection (bonding) between mother and child. However, the exclusive breastfeeding coverage rate is still low due to failure to breastfeed. One of the factors that influence failure in the breastfeeding process can be caused by not releasing milk. The smoothness of breastfeeding is strongly influenced by psychological factors, namely anxiety. This study aims to analyze the relationship between anxiety and the smoothness of breastfeeding in breastfeeding mothers in Slahung District, Ponorogo Regency. Subjects and Method: A cross-sectional study was conducted in Slahung District, Ponorogo Regency in November 2022. A total of 83 breastfeeding mothers were selected for this study. The dependent variable is the smooth expulsion of breast milk. The independent variable is anxiety. The instrument used is a questionnaire. The data were analyzed by Chi-Square test and odds ratio (OR). Results: Anxiety affects the smooth release of breast milk in nursing mothers. Breastfeeding mothers who experience anxiety are at risk of experiencing a milk ejection process that is not smooth as much as 26.18 times compared to breastfeeding mothers who do not experience anxiety, and these results are statistically significant (OR= 26.18; 95% CI= 3.20 to 214.12; p<0.001). Conclusion: Anxiety affects the smooth release of breast milk in nursing mothers. Keywords: anxiety, smooth milk production. Correspondence: Annisa Nur Rohma, Midwifery Program Study, Faculty of Medicine, Universotas Airlangga, Indonesia. Jl. Mayjen Prof. Dr. Moestopo No. 47, Pacar Kembang, Tambaksari, Surabaya, East Java, 60132. Email: annisa.nur.rohma-2019@fk.unair.ac.id. Mobile: +6285708790065.